Enhancing bone regeneration: Exploring the potential of silicate chlorinated bioactive glasses and dehydration mechanisms - de Souza, Joyce Rodrigues [UNESP]; Kukulka, Elisa Camargo [UNESP]; dos Santos, Vêronica Ribeiro; Kito, Letícia Terumi; Trichês, Eliandra de Sousa; Thim, Gilmar Patrocínio; Borges, Alexandre Luiz Souto [UNESP]; Campos, Tiago Moreira Bastos (Elsevier, 2024)
This study aimed to compare two different compositions of sol-gel method-derived silicate chlorinated bioactive glasses - 45S5 and 58S - and explore the dehydration processes applied (lyophilization, lyophilization+calcination, and calcination). In the synthesis process, sodium metasilicate was used as a silica precursor, and it underwent ion exchange to form silicic acid. The samples underwent characterization through a variety of techniques, assessing their structural properties including Raman spectroscopy, X-ray diffraction, Fourier transform infrared spectroscopy, and scanning electron microscopy, and regarding its bioactivity by the apatite mineralization assay in simulated body fluid. Raman spectroscopy revealed the lyophilization process led to the formation of Q1, Q2, and Q3 silicate structural units for both glasses, but following calcination these reacted to form solely Q2 units - as in the calcined-only glasses. X-ray diffraction analysis confirmed the amorphous nature of the 58S glass, while the 45S5 glass exhibited strong crystalline reflections, including a characteristic peak of sodium chloride. The apatite mineralization assay proved the high bioactivity of the produced glasses. The lyophilized only exhibited rapid hydroxyapatite conversion as a reflection of their structural units containing Q1 structures and of their porous microstructure. The calcined and lyophilized-calcined glasses formed calcium phosphate chloride (Ca2PO4Cl) as an intermediated phase in the glass conversion process. For the 45S5 glass in which both dehydration processes were applied, the intermediated phase led to pH equilibrium of the SBF solution. These findings contribute to the understanding of the structural and compositional properties of silicate chlorinated bioactive glasses synthesized via the sol-gel method. The evaluated glasses show potential for use in bone regeneration applications, with their bioactivity and structural characteristics playing key roles in promoting tissue healing and bonding with bone.
Keywords: Calcination; Glass; Spectroscopy; X-ray methods